Photovoltage and photocurrent spectroscopy of luminescent porous silicon - Vakulenko, O.V.; Kondratenko, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Measurements of photoconductivity, photovoltage and photoluminescence spectra of porous silicon/c-Si structures are carried out. It is shown that the shape of the photoconductivity and photovoltage spectra is caused mainly by bulk properties of porous silicon. Two components of the photovoltage spectral dependence caused by porous silicon are observed. On the contrary, the one photoconductivity component is revealed. Moreover, the photoconductivity spectrum shape is found to depend on the value of the bias voltage and differ from the photovoltage spectrum in the short-wave region. The obtained results are explained within the model where the por-Si is considered as composite system of crystallites embedded in amourphous matrix of silicon compounds.